2019
DOI: 10.1155/2019/1960609
|View full text |Cite
|
Sign up to set email alerts
|

Modified Cervicofacial Flap for Large Cheek Defect Reconstruction under Local Anesthesia

Abstract: The cervicofacial flap was first described in 1969. For the past several years, it has been the flap of choice for the reconstruction of facial defects especially cheek defects. In recent years, with the advent of microvascular free flap tissue transfer, the use of a cervicofacial flap has been sparse. This article highlights the importance and application of locoregional flaps such as a cervicofacial flap in the reconstruction of soft tissue defects on a face. This case was unique from the reconstruction poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has been reported that the method was performed under local anesthesia. 7 In our case, as the zygomatic bone resection was relatively small, satisfactory results were obtained using cervicofacial flap. However, in cases where the zygomatic bone needs to be largely resected, it is considered necessary to perform microvascular free flap transfer, such as an osteocutaneous scapular flap.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It has been reported that the method was performed under local anesthesia. 7 In our case, as the zygomatic bone resection was relatively small, satisfactory results were obtained using cervicofacial flap. However, in cases where the zygomatic bone needs to be largely resected, it is considered necessary to perform microvascular free flap transfer, such as an osteocutaneous scapular flap.…”
Section: Discussionmentioning
confidence: 51%
“…The method does not require special techniques, such as vascular anastomosis, and can shorten the surgery time. It has been reported that the method was performed under local anesthesia 7 . In our case, as the zygomatic bone resection was relatively small, satisfactory results were obtained using cervicofacial flap.…”
Section: Discussionmentioning
confidence: 52%
“…The modified cervicofacial flaps was used by Kaplan in 1978 for coverage of defects following removal of cancers of the head and neck. 2 This flap had undergone modifications based on the plane of dissection either superficial or deep to SMAS 3 . The supra- SMAS flaps depend on the rich subdermal plexus of vessels, and the infra- SMAS flaps rely upon more reliable large perforator branches from facial and transverse facial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, such patients will benefit from locoregional flaps such as cervicofacial flap that can be done over a reduced operating time and considerable postoperative recovery time. This flap technique had gone through various modifications since its introduction by Esser et al in 1918 2 The modifications are in relation to superficial musculo-aponeurotic system (SMAS) plane dissection whether superficial or deep to it 3 . It has robust random blood supply and it is usually inferiorly based.…”
Section: Introductionmentioning
confidence: 99%